Victimización durante la pandemia de COVID-19 y síntomas de trauma psicológico en adolescentes tempranos y tardíos: el papel mediador de la soledad - Magro Lazo, Giancarlo Carlos (2024)
This study aims to analyze the effect of victimization suffered during the COVID-19 lockdown on psychological trauma in early and late adolescents. The sample of this study comprised of 933 Peruvian adolescents, 45.5% (n= 423) were males and (54.5%) (n= 506) were females. 44.5% (n=415) were in early adolescence (12 to 13 years) and 55.5 % (n=518) were in late adolescence (14 to 17 years). Data was collected online during the COVID-19 lockdown. Results show that early adolescents who have suffered victimization have higher probabilities of suffering psychological trauma than late adolescents compared to non- victims. In addition, loneliness is observed to play a significant role as a mediator in the relationship between victimization and psychological trauma in Early Adolescents (B = .69, SE = 0.08, CI [ .53, .86]) and late adolescents (B = .66, SE = 0.07, CI [.51, .81]). Results suggests that the cost-benefit of COVID 19 lockdown should be reconsidered. Social distance could had made difficult for adolescents to stablish interpersonal relationships and solve conflicts associated with victimization. Loneliness could be an expression of these difficulties and therefore explain symptoms of psychological trauma. Finally, results are discussed in order to prevent the harmful effects of the pandemic and the measures taken on adolescent mental health, especially in middle- and low-income countries.